2017
DOI: 10.1080/16066359.2017.1288806
|View full text |Cite
|
Sign up to set email alerts
|

Gambling behavior in alcohol-serving and non-alcohol-serving-venues: a study of electronic gaming machine players using account records

Abstract: Aim: Contextual factors, such as venue characteristics appear to influence gambling behavior. However, few studies have compared the relationship between gambling behavior in alcohol-serving venues (ASVs) and nonalcohol serving venues (NASVs). The aim of the study was to examine individual gambling behavior in ASVs and NASVs.Method: A repeated-measures design was used to examine individual gambling behavior in ASVs and NASVs covering a month. The sample comprised 1,452 observations of 726 individuals (25.2% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…Similar results have been obtained in nationally representative samples of citizens in which more frequent use of alcohol was significantly correlated to more gambling-related problems in the US (French, Maclean, & Ettner, 2008) and the UK (Griffiths, Wardle et al, 2010). A recent study using behavioural tracking data from player cards also reported that slot machine gamblers lost more money in environments that sold alcohol compared to those environments that did not (Leino, Sagoe et al, 2017).…”
Section: Introductionsupporting
confidence: 76%
“…Similar results have been obtained in nationally representative samples of citizens in which more frequent use of alcohol was significantly correlated to more gambling-related problems in the US (French, Maclean, & Ettner, 2008) and the UK (Griffiths, Wardle et al, 2010). A recent study using behavioural tracking data from player cards also reported that slot machine gamblers lost more money in environments that sold alcohol compared to those environments that did not (Leino, Sagoe et al, 2017).…”
Section: Introductionsupporting
confidence: 76%
“…Such factors may shift gamblers along the continuum to higher levels of risk or problem severity (Hing et al 2014). Alcohol intoxication is associated with increased motivations to gamble, more risky gambling behaviour and higher loses, whilst gambling advertising and promotions have been found to remind problem gamblers about gambling and arouse urges to gamble (Barrett et al 2015;Binde 2009;Leino et al 2017). For some individuals, higher losses may serve as a pathway to future gambling problems if they chase their losses (Lesieur 1984).…”
Section: Discussionmentioning
confidence: 99%
“…One way forward in the field would be for gaming operators to provide access to real-time behavioral tracking data of players so that researchers can conduct secondary analysis of player behavior in relation to specific in-game structural characteristics. This has already started to happen in the gambling studies field with analyses of the impact of structural and situational characteristics on the behavior of slot machine players [ 77 , 78 ].…”
Section: Concluding Commentsmentioning
confidence: 99%